Utilization of waste glycerol as a carbon source for Pichia pastoris cultivation - Singsun, Nongnuch; Kanongnuch, Chartchai; Leksawasdi, Noppol; Pratanaphon, Ronachai (Food and Applied Bioscience Journal, 2017)
Waste glycerol is a by-product of the biodiesel production process. Therefore, waste glycerol price is very inexpensive. The feasibility of cultivating Pichia pastoris using waste glycerol as a carbon source was investigated. In this study, the composition of waste glycerol from 2 sources, E-ester company, Chiang Rai and Maecham pork cracker community enterprise, Chiang Mai was analyzed. The average glycerol content was 27.70% and 29.82%, respectively. The simple methods to pretreat the waste glycerol were employed. Then the effect of treated and untreated waste glycerol on P. pastoris growth compared with pure glycerol was investigated. The suitable concentration of waste glycerol for P. pastoris cultivation was also assessed. Media containing 1, 2 and 5% (v/v) waste glycerol were used to cultivate P. pastoris. The highest dry cell weight was achieved using 5% untreated waste glycerol. The maximum dry cell weight using waste glycerol from E-ester company, Chiang Rai and Maecham pork cracker community enterprise, Chiang Mai were 11.47 and 14.38 g/L, respectively. The high density of biomass obtained from fermentation in a 5-L bioreactor by using waste glycerol as a carbon source without any negative effect. This study revealed that waste glycerol from E-ester company, Chiang Rai and Maecham pork cracker community enterprise, Chiang Mai can be directly used as a carbon source for P. pastoris cultivation.